Development of a nomogram for predicting the intraperitoneal rupture of necrotic collection in patients with necrotizing pancreatitis - Li, Gang; Liu, Yang; Liu, Zirui; Bu, Minchun; Li, Kaiming; Yang, Jie; Zhang, Jingzhu; Zhou, Jing; Ye, Bo; Gao, Lin; Tong, Zhihui; Li, Weiqin (Frontiers in Medicine, 2025)
ObjectivesIntraperitoneal rupture of necrotic collection (IRNC) is an extremely rare and severe complication in patients with necrotizing pancreatitis. This study aimed to describe the clinical characteristics of intraperitoneal rupture of necrotic collection and develop a distinct model for predicting the risk of IRNC.MethodsThis is a single-center, retrospective study. All consecutive patients with a primary diagnosis of necrotizing pancreatitis between January 2017 and December 2018 were screened. A nomogram was developed by multivariable logistic regression, and predictive discrimination, calibration, and clinical applicability were tested.ResultsOf the 181 patients included, 20 (11%) patients developed intraperitoneal rupture of necrotic collections spontaneously during hospitalization (IRNC group). Compared with the non-IRNC group, patients in the IRNC group received more emergency open necrosectomy, and had a higher incidence of major complications and longer hospital stays. Variables associated with intraperitoneal rupture of necrotic collections included body temperature, total protein, white blood cell, and fibrinogen degradation products. A clinical prediction nomogram was developed for predicting rupture, and it exhibited better discrimination than the currently available parameters, with an area under the ROC curve of 0.897 (95%CI: 0.835–0.958).ConclusionWe have developed a nomogram to identify patients who are at risk of IRNC. Further studies are needed to externally validate and include more data to enhance the applicability and generalizability of the nomogram.